Analysis of risk factors for neurological dysfunction in patients with acute aortic dissection type A: data from the German Registry for Acute Aortic Dissection Type A (GERAADA) - Conzelmann, Lars Oliver; Kallenbach, Klaus; Karck, Matthias (European journal of cardio-thoracic surgery, 2012)
AbstractOBJECTIVES. Acute aortic dissection type A (AADA) is associated with major adverse events, such as transient or persistent neurological dysfunction (ND
Published 01 March 2012
Gesehen am 05.10.2018